Revisiting Stål's thoughts: formalizing the ictericus group in Euschistus (Euschistus) (Hemiptera: Heteroptera: Pentatomidae) - Paim, Marcelo R.; Grazia, Jocelia; Rider, David. A.; Bianchi, Filipe M. (Zootaxa, 2022)
Euschistus Dallas is distributed throughout the Western Hemisphere and is composed of 67 species in three subgenera: Euschistomorphus Jensen-Haarup, Lycipta Stål, and the nominate subgenus. Euschistus (Euschistus) includes several economically important species. Due to the lack of a phylogenetic analysis for the subgenus Euschistus, its groupings are based primarily on male genitalia. In this paper, the following Nearctic taxa that were first grouped together by Stål (1872), namely E. ictericus (Linnaeus), E. variolarius (Palisot de Beauvois), E. servus servus (Say), E. servus euschistoides (Vollenhoven), and E. tristigmus tristigmus (Say), are reviewed and redescribed. Several other similar, and probably related, taxa are also included in this study: E. tristigmus luridus (Dallas), E. inflatus Van Duzee, and E. latimarginatus Zimmer. Morphological patterns pertaining to the internal and external male and female genitalia allowed us to formalize the ictericus group to include the above-mentioned species (except E. tristigmus). The morphological overlap between the subspecies and sympatric areas of distribution have led us to consider E. servus euschistoides as a junior synonym of E. servus servus, and to corroborate the synonymy first proposed by Uhler (1861) of E. tristigmus luridus under E. tristigmus tristigmus.